Galaxy : mapping the cosmos - Geach, James (Reaktion Books Ltd, 2014)
Each night, we are able to gaze up at the night sky and look at the thousands of stars that stretch to the end of our individual horizons. But the stars we see are only those that make up our own Milky Way galaxy-but one of hundreds of billions in the whole of the universe, each separated by inconceivably huge tracts of empty space. In this book, astronomer James Geach tells the rich stories of both the evolution of galaxies and our ability to observe them, offering a fascinating history of how we've come to realize humanity's tiny place in the vast universe. Taking us.